Effect of Bio-fertilizers on Bio-nutrients, Nitrogen, Total Protein, Extractable Lipid and Mineral Contents of Cultivated Variety of Fenugreek (Trigonella foenum graecum Linn.) - U.S. Mishra2, Nishant Mishra1*, Chandra Pal Singh2 and (Journal of Phytology, 2011)
Green house experiments were conducted in Botany Department of Bareilly College, Bareilly during the growing season of 2003 and 2004 on a cultivated varieties of fenugreek to evaluate the effect of two selected bio-fertilizers (Azatobactor and Azospirillum) on total nitrogen, total protein, extractable lipid and some mineral contents of fenugreek seeds. The selected experimental variety was Pusa early bunching which was commonly cultivated in Bareilly region. Application of both the fertilizers either alone and in combination exhibited in general a considerable improvement in above bio-nutrient parameters of seeds as compared to their respective control. A balanced and judicious use of these bio-fertilizers is recommended to the farmers to enhance nutritive value of fenugreek seeds.